2019
DOI: 10.5056/jnm19060
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Symptoms, Quality of Life, and Gastric Emptying in Dyspeptic Patients

Abstract: Background/Aims Association between symptoms, quality of life and gastric emptying in dyspepsia is inconsistent in the literature. The aim of our study is to investigate if gastric emptying is associated with specific symptoms and quality of life in dyspeptic patients. Methods We reviewed retrospectively gastric emptying measured by 13 C-labelled octanoate breath testing for more than 6 hours in 198 consecutive patients with dyspepsia complaints. Gastrointestinal symptoms were assessed using a 5-points Likert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
31
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 54 publications
4
31
3
Order By: Relevance
“…In addition, pyloric distensibility correlated negatively with gastroparesis symptoms, including nausea, 75,79 gastric fullness, 75,77 early satiety, 75,77 and quality of life 75,77 . This contrasts with gastric emptying measurement which is poorly correlated with symptoms or quality of life 71‐73 (LE 3). This suggests therefore that pyloric distensibility may be a clinically relevant tool in a subset of gastroparetic patients to better identify precisely one of the underlying mechanisms involved in gastric retention 17,80 …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, pyloric distensibility correlated negatively with gastroparesis symptoms, including nausea, 75,79 gastric fullness, 75,77 early satiety, 75,77 and quality of life 75,77 . This contrasts with gastric emptying measurement which is poorly correlated with symptoms or quality of life 71‐73 (LE 3). This suggests therefore that pyloric distensibility may be a clinically relevant tool in a subset of gastroparetic patients to better identify precisely one of the underlying mechanisms involved in gastric retention 17,80 …”
Section: Resultsmentioning
confidence: 92%
“…Clinical diagnosis of gastroparesis may be challenging as symptoms patterns and severity are poorly correlated with gastric emptying 71‐73 . Historically, the role of pylorus in gastric emptying delay and symptom generation has been highlighted.…”
Section: Resultsmentioning
confidence: 99%
“…6,16 However, other studies revealed no or little difference in symptoms between patients with or without delayed gastric emptying. 5,17,18 Also, FD subgroups are not differentially related to abnormalities of stomach motor function. 19 Although SPECT can quantify the amount of remaining material in the stomach, it cannot distinguish a patient with FD from that with idiopathic gastroparesis.…”
mentioning
confidence: 94%
“…In this issue of Journal of Neurogastroenterology and Motility, Wuestenberghs et al 15 assessed association between symptoms and gastric emptying in 198 patients with dyspepsia. The main findings were that there was no association between symptoms, quality of life, and gastric emptying in their population.…”
mentioning
confidence: 99%
“…Specifically, a populationbased study applying the Rome III showed FD overlap both with IBS and GERD had a significant impact on bodily pain. 14 In addition, Wuestenberghs et al 15 reported that patients with IBS present poorer quality of life (GIQLI scores of 71.9 points compared to 83.6 without overlap with IBS, P = 0.002). As mentioned above, these factors may be confounders that distort the association among gastric emptying, symptoms and HRQOL.…”
mentioning
confidence: 99%